Leading Innovative Work-Behavior in Times of COVID-19: Relationship Between Leadership Style, Innovative Work-Behavior, Work-Related Flow, and IT-Enabled Presence Awareness During the First and Second Wave of the COVID-19 Pandemic - Coun, Martine J. H.; Edelbroek, Robin; Peters, Pascale; Blomme, Robert J. (Frontiers in Psychology, 2021)
Aim – The present study contributes to the conversation on remote (home) working, leadership, and innovation in times of COVID-19 by examining the mediating role of work-related flow in the relationship between empowering and directive leadership, on the one hand, and innovative work-behavior, on the other, and the moderating role of IT-enabled presence awareness in two lockdown periods during the pandemic. Method – We employed PLS-SEM analysis to analyze the perceptions, experiences, and behaviors of a group of employees (N= 257) regarding the study’s core variables during two phases of the COVID-19 pandemic (summer 2020 and autumn 2020). Results – In line with expectations, in the earlier phase of the pandemic, empowering leadership had both a positive direct and indirect relationship with innovative work-behavior via work-related flow, whereas directive leadership only had a negative direct relationship with innovative work-behavior. In the second phase, however, empowering leadership only had a positive indirect relationship with innovative work-behavior, running via work-related flow. Moreover, directive leadership was both directly and indirectly negatively related to innovative work-behavior, via work-related flow. In contrast to our expectations, IT-enabled presence awareness did not play a moderating role in these relationships in any phase. Discussion – Our findings underline the importance of empowerment in sustaining innovative work-behavior, particularly in intense and enduring remote work contexts, as this can amplify employees’ ability, motivation and opportunity to generate, share and implement novel ideas. In remote work contexts, empowering leadership can particularly foster innovation indirectly via work-related flow, which was also shown to be an increasingly important underlying mechanism across time periods. Directive leadership, in contrast, can reduce work-related flow and, therefore, hinder innovation. our study did not find evidence for the moderating role of employees’ perceptions of IT-enabled presence awareness. Conclusion – We conclude that regardless of the IT-quality, the leadership style chosen plays an important role in innovative work-behavior in remote work-contexts, particularly in view of the divergent effects of empowering and directive leadership on work-related flow in enduring and intense remote work contexts.